Brain metabolism in tau and amyloid mouse models of Alzheimer's disease: An MRI study. (29th May 2021) - Wei, Zhiliang; Xu, Jiadi; Chen, Lin; Hirschler, Lydiane; Barbier, Emmanuel L.; Li, Tong; Wong, Philip C.; Lu, Hanzhang
Abstract : Alzheimer's disease (AD) is the leading cause of cognitive impairment and dementia in elderly individuals. According to the current biomarker framework for "unbiased descriptive classification", biomarkers of neurodegeneration, "N", constitute a critical component in the tri‐category "A/T/N" system. Current biomarkers of neurodegeneration suffer from potential drawbacks such as requiring invasive lumbar puncture, involving ionizing radiation, or representing a late, irreversible marker. Recent human studies have suggested that reduced brain oxygen metabolism may be a new functional marker of neurodegeneration in AD, but the heterogeneity and the presence of mixed pathology in human patients did not allow a full understanding of the role of oxygen extraction and metabolism in AD. In this report, global brain oxygen metabolism and related physiological parameters were studied in two AD mouse models with relatively pure pathology, using advanced MRI techniques including T2 ‐relaxation‐under‐spin‐tagging (TRUST) and phase contrast (PC) MRI. Additionally, regional cerebral blood flow (CBF) was determined with pseudocontinuous arterial spin labeling. Reduced global oxygen extraction fraction (by −18.7%, p  = 0.008), unit‐mass cerebral metabolic rate of oxygen (CMRO2 ) (by −17.4%, p  = 0.04) and total CMRO2 (by −30.8%, p  < 0.001) were observed in Tau4RΔK mice—referred to as the tau AD model—which manifested pronounced neurodegeneration, as measured by diminished brain volume (by −15.2%, p  < 0.001). Global and regional CBF in these mice were not different from those of wild‐type mice ( p  > 0.05), suggesting normal vascular function. By contrast, in B6;SJL‐Tg [APPSWE]2576Kha (APP) mice—referred to as the amyloid AD model—no brain volume reduction, as well as relatively intact brain oxygen extraction and metabolism, were found ( p  > 0.05). Consistent with the imaging data, behavioral measures of walking distance were impaired in Tau4RΔK mice ( p  = 0.004), but not in APP mice ( p  = 0.88). Collectively, these findings support the hypothesis that noninvasive MRI measurement of brain oxygen metabolism may be a promising biomarker of neurodegeneration in AD. Abstract : The Alzheimer's disease (AD) model with neurodegeneration (i.e. brain atrophy) exhibited diminished oxygen extraction, while in the AD model without neurodegeneration the brain's oxygen extraction was unchanged, supporting the potential of brain oxygen extraction as a biomarker for neurodegeneration in AD.